OPTIMALISASI PENGEMBANGAN BAKAT MINAT SANTRI MEMBACA KITAB KUNING DENGAN METODE NUBDZATUL BAYAN - Rosi, Fathor; Mufarrohah, Isnainil; Mirin Hartono (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to optimize the development of students' talents and interests in reading yellow books at the Sumber Bunga Islamic Boarding School through the Nubdzatul Bayan method. The scope of the study includes an analysis of the applied learning methods and their impact on students' abilities in understanding yellow books. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the application of the Nubdzatul Bayan method significantly increases students' interests and abilities in reading yellow books. Students involved in this program show a better understanding of classical texts, as well as sharper analytical skills. The conclusion of this study emphasizes the importance of the right method in developing students' talents and interests, as well as the need for ongoing support from the boarding school supervisor to create a conducive learning environment.